INDIA’S MARITIME DIPLOMACY IN THE SOUTHEAST ASIA - Aghnia Lailaturrahmi Noferius; Rika Isnarti; Haiyyu Darman Moenir (Dauliyah Journal of Islamic and International Affairs, 2020)
This research aims to analyze maritime diplomacy of India in Southeast Asia from 2014 to 2017. This research utilizes the concept of maritime diplomacy by Christian Le Mière. Christian Le Mière that classified maritime diplomacy into three categories which are co-operative maritime diplomac, indicated by humanitarian assistance/disaster relief, goodwill visit, training, and joint exercise and Joint Maritime Security Operations; persuasive maritime diplomacy and coercive maritime diplomacy. This research utilizes qualitative research using secondary data analysis from library research. Maritime diplomacy is chosen because there are increasing activity in the India’s maritime security and trading aspect in the period of 2014-2017. This study found that maritime diplomacy conducted by India fulfilled four indicators of co-operative maritime diplomacy, namely: humanitarian assessment/disaster relief, goodwill visit, training, and joint exercise and Joint Maritime Security Operations with the Indian Navy as the main actor in maritime diplomacy to achieve Indian security interests and trade.